Heart rate variability series during physical activity analyzed with multifractal techniques - Ana María Aguilar-Molina; José Alberto Zamora-Justo; Fernando Angulo-Brown; Alejandro Muñoz-Diosdado (Journal of Physics: Complexity, 2024)
Our study uses multifractal techniques to analyze time series of heart rate variability series ( RR time series) during rest and physical activity. Subsets of the RR time series data were extracted for each stage. The multifractal spectra of the RR time series data were constructed using the method developed by Chhabra and Jensen. Then, parameters such as width, symmetry, and curvature of the multifractal spectra were calculated. The multifractal spectra obtained at resting stage were broad, skewed to the right, and they had small curvatures around in the maximum. On the contrary, the subsets of the RR time series obtained during physical activity were narrow, skewed to the left, and showed an increased curvature value around the maximum. In addition, these multifractal spectrum parameters shown significant differences in series of subjects who perform physical activity regularly and sedentary. Furthermore, the results obtained from this study were compared with data from previous works involving patients with congestive heart failure and healthy subjects.